'It's a resting place, where our spirits go': Bringing back lost ancestor memories to Western Australia's Great Southern – Noongar boodja. (1st October 2016) - Huebner, Sharon; Flowers, Ezzard
This article considers the dynamic relationship between Aboriginal Australia identity, western history and the recuperation of lost ancestral memories. In recent decades many Australian cultural institutions have supported Aboriginal community groups in the revival of Aboriginal languages, songs and stories. The reclamation of heritage from archival collections has helped strengthen Aboriginal claim and control of ancestor histories – especially when significant materials are returned to people of a descendant community and given meaningful social context. Often set in place from these interactions are cultural protocols and ethics formulating future material access, return and usage. Looking more closely at intercultural practices of repatriation, this article relates Aboriginal pathways of ancestral memory restoration (and invention of memory) to living story. In particular, it examines the cultural decision-making of two Australian Aboriginal family groups – Wirlomin Minang (Noongar) families from the Great Southern of Western Australia and Gunai Kurnai (Koorie) families from the Gippsland region of Victoria – who characterize kin reactions to the returned colonial historiography of their shared ancestor Bessy Flowers (c. 1849–95), as well as family grief and shame at her absent memory. The difference between the archival material of photographs and letters that represent Bessy and the ways her Wirlomin Minang and Gunai Kurnai families imagine themselves created context for the mixed-media co-production, No Longer a Wandering Spirit. This article explores how intercultural efforts to strengthen family story might widen circles of knowledge about Aboriginal cultural dislocation, historical exclusion and the ever-present action of resistance and recovery.